2016
DOI: 10.1177/1932296816633232
|View full text |Cite
|
Sign up to set email alerts
|

Attributes Influencing Insulin Pen Preference Among Caregivers and Patients With Diabetes Who Require Greater Than 20 Units of Mealtime Insulin

Abstract: Background: This study compared patient preference for Humalog® KwikPen™ 200 units/mL (insulin lispro; hereafter, IL 200 pen; Eli Lilly and Company, Indianapolis, IN) versus the Humalog KwikPen 100 units/mL (insulin lispro; hereafter, IL 100 pen; Eli Lilly and Company, Indianapolis, IN) in patients with diabetes requiring >20 units of mealtime insulin and diabetes caregivers. This study also determined which attributes had the greatest influence on pen preference selection. Methods: In this 2-period, crossover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
(41 reference statements)
4
17
0
Order By: Relevance
“…Findings from this Italian sample provide insight into patient preferences associated with rapid-acting insulin concentration. Results are consistent with those from previous studies showing a preference for concentrated over standard insulin [33,35]. The findings of the current study add to previous research by demonstrating the strength of this preference, while providing utility values that can represent patient preference in cost-effectiveness analyses comparing insulin formulations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Findings from this Italian sample provide insight into patient preferences associated with rapid-acting insulin concentration. Results are consistent with those from previous studies showing a preference for concentrated over standard insulin [33,35]. The findings of the current study add to previous research by demonstrating the strength of this preference, while providing utility values that can represent patient preference in cost-effectiveness analyses comparing insulin formulations.…”
Section: Discussionsupporting
confidence: 89%
“…A literature search was conducted to support health state content and guide subsequent discussions with clinicians. The literature search focused on standard (100 units/mL) and concentrated (200 units/mL) insulin lispro product information [18], glide force (i.e., the amount of effort required to press the pen's injection button) [31], and patient perceptions of standard and concentrated insulin [32][33][34][35].…”
Section: Health State Developmentmentioning
confidence: 99%
“…Consistent with previous studies examining preferences for features of insulin pen devices that included both patients with diabetes and caregivers, this study found that ease of use is a key attribute that influences preferences. 27,28 A device that is easy to use is likely to be associated with fewer errors in administration. Indeed, one study found that >94% of caregivers and 93% of acquaintances delivered full doses of nasal glucagon, whereas only 13% of caregivers and 0% of acquaintances delivered full doses of the existing injectable glucagon.…”
Section: Discussionmentioning
confidence: 99%
“…Because the volume is reduced by half in case of switching from U-100 to U-200, the throw of the plunger is likewise reduced by the same magnitude for any given dose of insulin. People with diabetes expressed preference for the use of a U-200 concentrated insulin pen compared to a U-100 insulin pen because of an improved injection experience related to reduced injection volume and reduced injection force of the pen [24].…”
Section: Easier Delivery Of Larger Dosesmentioning
confidence: 99%
“…The pen provided for Lispro-U200 was found to be preferred over the pen used for Lispro-U100. Reasons for this preference included more units per pen (pen changes are half as frequent), reduced injection force, and a 50% reduction in injection volume [13,24].…”
Section: Insulin Lispro U-200mentioning
confidence: 99%